Use of pioglitazone in diabetic patients with Alzheimer's disease-related cognitive impairment (Research, Society and Development, 2023)
Introduction: Studies have suggested that the use of pioglitazone in patients with type 2 diabetes (DM2) was associated with a significantly lower risk of cognitive deterioration. Thus, this article aims to elucidate the effect of pioglitazone on cognition in patients with type 2 diabetes. Materials and methods: This is an integrative review, in which the guiding question was "Is pioglitazone able to reduce the progression of dementia in patients with type 2 diabetes mellitus?" The search for articles was conducted on PubMed using the terms "pioglitazone," "dementia," and "Alzheimer's" combined with Boolean operators. Results and Discussion: It is possible to infer that pioglitazone is associated with a lower risk of dementia progression in patients with recently diagnosed type 2 DM, having positive effects also in individuals with heart disease and stroke.  Final considerations: Therefore, the use of pioglitazone has benefits in reducing dementia depending on the comorbidities that the individual has, and it is not openly recommended for every type of patient. Future studies should analyze the best patient profile for the administration of the drug, so that its maximum effectiveness is achieved.